2017
DOI: 10.4049/jimmunol.1601519
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Microbiome on Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) is characterized by the autoimmune destruction of pancreatic β cells. The rapid rise in T1D incidence during the past 50 y suggests environmental factors contribute to the disease. The trillion symbiotic microorganisms inhabiting the mammalian gastrointestinal tract (i.e., the microbiota) influence numerous aspects of host physiology. In this study we review the evidence linking perturbations of the gut microbiome to pancreatic autoimmunity. We discuss data from rodent models demonstratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(73 citation statements)
references
References 59 publications
0
67
1
3
Order By: Relevance
“…Even though studies have shown that intestinal dysbiosis can affect gut permeability via their metabolites and play a role in T1D development, there is no evidence for the real role of intestinal microbiota in the development of autoimmunity to β ‐cells and in tissue damage in humans. Additional studies are needed to find the specific microbial ligands that signal through immune cells in the gut and might be involved in the autoreactivity to β ‐cells …”
Section: Type 1 Diabetesmentioning
confidence: 99%
“…Even though studies have shown that intestinal dysbiosis can affect gut permeability via their metabolites and play a role in T1D development, there is no evidence for the real role of intestinal microbiota in the development of autoimmunity to β ‐cells and in tissue damage in humans. Additional studies are needed to find the specific microbial ligands that signal through immune cells in the gut and might be involved in the autoreactivity to β ‐cells …”
Section: Type 1 Diabetesmentioning
confidence: 99%
“…Previous studies have established a correlation between seroconversion and chronic inflammation resulting from impaired gut barrier function and increased intestinal permeability, which is suggested as a hallmark of T1D (Vaarala et al, 2008). Given the overarching influence of gut bacteria on human health, including intestinal permeability and its regulatory role in autoimmunity, the role of the microbiota in T1D development has been recently explored (Knip and Siljander, 2016; Kostic et al, 2016; Paun et al, 2017). The microbiota of the human intestinal tract is comprised of bacteria, fungi, and eukaryotic and bacterial viruses (bacteriophages).…”
Section: Introductionmentioning
confidence: 99%
“…7 Moreover, many metabolic syndrome diseases are now recognized as having an inflammatory component attributable to Western lifestyle, including fatty liver disease, cardiovascular diseases, hyperlipidemia, cancer, and type 1 and 2 diabetes. [12][13][14][15]16…”
mentioning
confidence: 99%